The Effect of Uchikomi Seoi-Nage Exercise Using Kettler Rubber for 8 Weeks on Performance Physical Ability Judoka - Candra Kurniawan; Sugiharto Sugiharto; Surisman Surisman (IKIP Budi Utomo Malang, 2022)
This study aimed to analyze the effect of uchikomi movement exercise using kettler rubber to improve male judoka's physical abilities. This study uses an experimental method. A total of 22 male judoka participated as study samples and were randomly divided into two groups. The experimental group (21.8±1.78 years, 1.70±0.06 m, 71.1±13.5 kg) and control group (21.4±2.30 years, 1.72±0.05 m, 67.4±7.76 kg). The exercise program was carried out for 8 weeks with a frequency of 3 times/week. After warming up and before core judo training, the experimental group was treated with uchikomi movement training using kettler rubber. Meanwhile, the control group continued regular judo training. The statistical analysis procedure used an ANOVA test to determine the difference and comparison of pre-test and post-test mean values in experimental and control groups with a significance level (p<0.05). The results showed that parameter difference in the average value of experimental and control groups was significant on the performance of leg power and VO2Max endurance. In comparison, no significant differences occur in handgrip strength, flexibility, and speed. This study concludes that uchikomi seoi-nage movement exercise using a Kettler rubber produces changes in the performance of judoka physical abilities. However, a significant difference occurred in the performance of leg power and VO2Max endurance